FIGURES OF SPEECH; METAPHOR USED IN HOUSING ADVERTISEMENTS IN âTHE POINTâ NEWSPAPER IN NOVEMBER 2009 - Wahyu, Widianto; Dias, Susanto Andris (ETERNAL, 2010)
Abstract M. Wahyu Widiyanto and Dias Andris Susanto. Figures of Speech;Â Metaphor Used in Housing Advertisements in âTHE POINTâ Newspaper in November 2009. The objectives of the study are (1) to know the kinds of metaphor are used in housing advertisements, (2) to know how metaphors are used in the realizing meaning. The object of this study was the housing advertisements in âTHE POINTâ in November 2009. The data were words, phrases and sentences in the housing advertisements that contain metaphors. This research was meant to analyze metaphor used in housing advertisements. To make it more effective, the analysis was conducted through several steps. First, the advertisements from the Jakarta Post newspaper were collected and then those advertisements were arranged in data cards as an attempt to know the metaphor and separated based on the types. Finally, the classified phrases or sentences in the Advertisements were identified and were interpreted to get the final result. The kind of research does not focus on numbers or statistica